Serviços ecossistêmicos culturais na despoluição de córregos urbanos – análise da bacia do córrego Charles de Gaulle (São Paulo) - Flausino, Fabio Richard (2018)
Urban rivers offer a few benefits to society. The advanced process of urban river degradation and its impacts on large cities has mobilized society to collect alternatives from the public power to solve this environmental problem. Since 2007, the Córrego Limpo Program has been contributing as an effective urban and environmental policy that enables society to recover the coexistence in harmony with the environment, minimizing the impact that the lack of urban planning caused to the streams of the city of São Paulo by the occupation of areas of springs and river banks. The evaluation of the activities of decontamination of the streams allows to verify the perception of the society by the sewage removal from the urban rivers, measured by means of ecosystem services. The objective of this research is to analyze the ecosystemic cultural services associated with the process of decontamination of urban streams of the Córrego Limpo Program by the perception of the interested parties. The identification and evaluation of the benefits provided in the decontamination of the Charles de Gaulle stream, one of the success stories of the Córrego Limpo Program, was carried out through exploratory qualitative research, integration of primary data from semi-structured interviews in the field, interpretation of secondary data from the company responsible for the depollution and subsidized by bibliographical survey of cultural ecosystem services in urban water depollution. The results of this research show the association between the stakeholder’s perception (residents, regulators and technicians of the sanitation company) on the benefits provided by the decontamination of the Charles de Gaulle stream and the cultural ecosystem services described in the literature. Finally, it is concluded that the depollution of an urban stream, in addition to revitalizing a degraded area, can promote cultural ecosystem services that are perceived and enjoyed by stakeholders.